2012
DOI: 10.1186/2162-3619-1-32
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of splenic marginal zone lymphoma of the CNS with high-dose therapy and allogeneic stem cell transplantation

Abstract: Therapy of indolent lymphomas with involvement of the central nervous system (CNS) has not been standardized so far. A 42-year old male patient presented with neurological signs because of leukemic splenic marginal zone lymphoma (SMZL) manifested in bone marrow, lymph nodes and CNS. Due to the aggressiveness of the disease and the young age of the patient, an intensive immunochemotherapy followed by high-dose therapy with busulfan, thiotepa and fludarabine and subsequent unrelated allogeneic stem cell transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…CFD results have shown to be consistent with the PFTs for the study of the alternation of the airflow before and after trachea-bronchial stent placements [15]. It is suggested that CFD may offer an important approach to assess the pulmonary function for the patients unsuitable for PFTs.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…CFD results have shown to be consistent with the PFTs for the study of the alternation of the airflow before and after trachea-bronchial stent placements [15]. It is suggested that CFD may offer an important approach to assess the pulmonary function for the patients unsuitable for PFTs.…”
Section: Discussionmentioning
confidence: 83%
“…The pressure drop is only 0.68 Pa for the healthy infant, which is close to the 0.70 ± 0.41 Pa for the healthy adult [15]. Even for the airway 17 generations deep in a healthy adult, the pressure drop is only 50.0 Pa while the flow rate is 28.3 L/min [26].…”
Section: Discussionmentioning
confidence: 87%
“…Regarding SMZL, there are only 5 cases with secondary CNS disease in the literature up‐to‐date, rising the number of such cases to seven, including ours, as shown on Table . In all instances, CNS symptoms were the trigger for diagnosis of systemic disease.…”
Section: Discussionmentioning
confidence: 82%
“…Historically, CFD has been used to describe airflow in upper airway reconstructive surgery, as well as for modeling fluid flow through blood vessels 4,2224 . Previous work has shown that CFD has the potential for use in evaluating treatment planning for airway interventions 4,25–27 . CFD allows for advanced diagnostic capabilities and is especially useful in cases involving multi-level or complex pathology.…”
Section: Discussionmentioning
confidence: 99%